ANALISIS PENGARUH HARGA SR-012, YIELD SR-012, INFLASI, DAN PRODUK DOMESTIK BRUTO TERHADAP PERMINTAAN SUKUK RITEL SR-012 - Daud Ibadurahman; Bahtiar Fitanto (Islamic Economics and finance in Focus, 2024)
The COVID-19 pandemic has shaken the economy and created a lot of uncertainty. Despite the economic downturn, the retail sukuk investment sector is growing. The demand for retail sukuk in this study is examined from the perspective of retail sukuk, the price and yield of SR-012, as well as from a macroeconomic perspective, inflation, and GDP. Therefore, the aim of this research is to determine the influence of price, yield, inflation, and GDP variables on the demand for retail sukuk SR-012. This study is quantitative research using secondary data obtained from The Indonesian Capital Market Institute (TICMI) and Badan Pusat Statistik (BPS). The research method employs multiple linear regression using E-views 12 software. The results of the study indicate that macroeconomic factors, inflation, and GDP, both does not have significant influence. On the other hand, the retail sukuk SR-012 factors, the price and yield of retail sukuk SR-012, have a significant negative impact on the demand for retail sukuk.